Heterogeneity Characteristics of Lacustrine Shale Oil Reservoir Under the Control of Lithofacies: A Case Study of the Dongyuemiao Member of Jurassic Ziliujing Formation, Sichuan Basin - Li, Peng; Liu, Zhongbao; Nie, Haikuan; Liang, Xinping; Li, Qianwen; Wang, Pengwei (Frontiers in Earth Science, 2021)
The lacustrine shale in the Dongyuemiao Member of the Fuling area of the Sichuan Basin is widely distributed and has huge shale oil resource potential. It has become one of the important replacement areas for shale oil exploration in China. This article investigates the key shale oil evaluation well, Well FY10, in Fuling area as the research object, using XRD mineral analysis, Rock-Eval, argon ion polishing-scanning electron microscope(SEM), mercury injection capillary pressure (MICP) and low pressure nitrogen adsorption methods to determine the heterogeneity of the pore system of the lacustrine shale in the Dongyuemiao Member. The mineral composition has a high degree of heterogeneity, and can be divided into two main shale lithofacies types: argillaceous shale and mixed shale. The porosity is ranges from 2.95% to8.43%, and the permeability is from 0.05 to 1.07×10-3μm2. The physical properties of mixed shale are obviously better than argillaceous shale. Inorganic mineral pores such as linear pores between clay minerals and calcite dissolution pores are mainly developed, while a small amount of organic pores are developed. The average total pore volume (Vp) is 0.038ml/g, the average specific surface area is 5.38m2/g, mesopores provide the main Vp (average 61.72%), and micropores provide the main specific surface area. TOC is the main parameter that controls the development of micropores. Clay minerals are the main contributors to mesopores and macropores. The organic-inorganic interaction in the process of diagenesis and hydrocarbon generation controls the formation of shale pore systems in different lithofacies.